N-[4-(β-d-Allopyranosyloxy)benzylidene]methylamine - Lv, Shi-Ming (International Union of Crystallography, 2009)
The title compound, C(14)H(19)NO(6), was synthesized by the condensation reaction between hecilid (4-formylphenl-β-d-allopyranoside) and methylamine in methanol. In the crystal structure, the pyran ring adopts a chair conformation and adjacent molecules are linked by intermolecular O—H⋯O and O—H⋯N hydrogen bonds, forming a three-dimensional network.